2lnx+4=5+lnx

Simple and best practice solution for 2lnx+4=5+lnx equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2lnx+4=5+lnx equation:


Simplifying
2lnx + 4 = 5 + lnx

Reorder the terms:
4 + 2lnx = 5 + lnx

Solving
4 + 2lnx = 5 + lnx

Solving for variable 'l'.

Move all terms containing l to the left, all other terms to the right.

Add '-1lnx' to each side of the equation.
4 + 2lnx + -1lnx = 5 + lnx + -1lnx

Combine like terms: 2lnx + -1lnx = 1lnx
4 + 1lnx = 5 + lnx + -1lnx

Combine like terms: lnx + -1lnx = 0
4 + 1lnx = 5 + 0
4 + 1lnx = 5

Add '-4' to each side of the equation.
4 + -4 + 1lnx = 5 + -4

Combine like terms: 4 + -4 = 0
0 + 1lnx = 5 + -4
1lnx = 5 + -4

Combine like terms: 5 + -4 = 1
1lnx = 1

Divide each side by '1nx'.
l = n-1x-1

Simplifying
l = n-1x-1

See similar equations:

| wx^2-w^2x^2=0 | | F(x)=5x^2+10x+12 | | 6t+8=26-3t | | 6y-1=8y-3y | | x/2=3-x/4 | | 8x^3-12x^2-10x+15= | | (x-1)/7-(x-3)/2=1 | | X=4x^2-9x+2 | | 4a+6=36 | | (x)=-2x^2+9x+5 | | x-.03x=158.92 | | 2g+6=6g-6 | | H(x)=-2x^2+9x+5 | | F(x)=4cos^2-6sin^2x | | x-3y=y+2x | | 4z-1=7z+4z | | (2x+16)=(4x-4) | | 3x^2+5=-3x+6 | | 7/8x-3/8=5/8 | | 6^-2=(1/36) | | x-y+2=x-2+y | | 70+x+30+2x-10=180 | | 11b+7=46 | | 6p-5=10p-25 | | x-6x=25 | | 9/14cos | | .9x-.9(5-x)=3.6 | | 8/2x=0 | | 5x(x-5)-11(x-5)= | | x*x=2*x | | 2v+42=-3(v-9) | | 3/10m-2/5=1/10. |

Equations solver categories